2003
DOI: 10.1016/s0014-5793(03)00413-7
|View full text |Cite
|
Sign up to set email alerts
|

Microwave radiation can alter protein conformation without bulk heating

Abstract: Exposure to microwave radiation enhances the aggregation of bovine serum albumin in vitro in a time-and temperature-dependent manner. Microwave radiation also promotes amyloid ¢bril formation by bovine insulin at 60 ‡C. These alterations in protein conformation are not accompanied by measurable temperature changes, consistent with estimates from ¢eld modelling of the speci¢c absorbed radiation (15^20 mW kg 31 ). Limited denaturation of cellular proteins could explain our previous observation that modest heat-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(141 citation statements)
references
References 23 publications
5
134
1
1
Order By: Relevance
“…There is currently no recognised biophysical basis for such non-thermal effects (Adair, 2002), although there have been suggestions that microwave fields might alter the rates of protein folding and unfolding (Bohr and Bohr, 2000;de Pomerai et al, 2003). This mechanism could plausibly explain the induction of a modest heat-shock response (de Pomerai et al 2000a, b;Leszczynski et al, 2002) via accumulation of partially unfolded proteins within cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no recognised biophysical basis for such non-thermal effects (Adair, 2002), although there have been suggestions that microwave fields might alter the rates of protein folding and unfolding (Bohr and Bohr, 2000;de Pomerai et al, 2003). This mechanism could plausibly explain the induction of a modest heat-shock response (de Pomerai et al 2000a, b;Leszczynski et al, 2002) via accumulation of partially unfolded proteins within cells.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the experimental results they concluded that MW radiation has the ability to change protein conformation by enhancing the kinetics of protein folding and denaturation, which could eventually lead to detrimental biological effects. De Pomerai et al (25) also showed that aggregation of protein bovine serum albumin could be enhanced by microwave radiation. Other different approaches have been considered regarding the interactions between RF/MW radiation and biological systems.…”
Section: Biological Mechanisms Of Rf/mw Actionmentioning
confidence: 98%
“…To probe the regulatory role of TF nodes in SRN pathways, we will ablate the function of selected TFs by feeding RNAi (e.g. for HSF-1) [45]. The efficacy of RNAi for each TF will be checked by monitoring reporter expression in TF-promoter::GFP fusion strains.…”
Section: Transcription Factor Nodesmentioning
confidence: 99%
“…The cyp-34A9 promoter contains a direct repeat of the nGAAn motif, but our cyp-34A9::GFP reporter strain shows poor heat inducibility at 35ºC, suggesting that this is not a functional HSF binding site. By contrast, the upstream promoter of cyp-35A2 contains a closer match (AAGCTCTT) to the HSF consensus binding site at around -100; the fact that a cyp-35A2::GFP reporter strain [37] shows strong heat inducibility at 35ºC suggests that this site may well be functional, though RNAi against HSF [45] will be needed to confirm this suggestion.…”
Section: A Case Study: Cyp-34a9 and Daf-16mentioning
confidence: 99%
See 1 more Smart Citation